1994
DOI: 10.1063/1.110877
|View full text |Cite
|
Sign up to set email alerts
|

Determination of band gap narrowing and hole density for heavily C-doped GaAs by photoluminescence spectroscopy

Abstract: The energy band gap narrowing effect in heavily C-doped GaAs was investigated using photoluminescence spectroscopy. The band gap was determined over the hole density range 1017–4×1020 cm−3 at 10 and 300 K. The band gap data at low temperatures confirm the available theoretical calculations up to 1020 cm−3. An unexpected temperature dependence of the observed band gap at high doping levels is discussed on the basis of carrier-phonon interactions. We present an analysis of the band gap narrowing effect that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…In this figure, we have also plotted the reported results for Zn, Be, and C doped GaAs measured at temperatures between 4.2 and 77 K, as the band gap shrinkage is independent of temperature [9,20]. The measured band gap shrinkage of carrier concentration of Be, C, and Zn-doped GaAs, exhibited consistent agreement between each other [9,14,18,24,25,28,37]. Fig.…”
Section: Band Gap Shrinkage Due To Doping Effectsupporting
confidence: 60%
See 2 more Smart Citations
“…In this figure, we have also plotted the reported results for Zn, Be, and C doped GaAs measured at temperatures between 4.2 and 77 K, as the band gap shrinkage is independent of temperature [9,20]. The measured band gap shrinkage of carrier concentration of Be, C, and Zn-doped GaAs, exhibited consistent agreement between each other [9,14,18,24,25,28,37]. Fig.…”
Section: Band Gap Shrinkage Due To Doping Effectsupporting
confidence: 60%
“…The hole concentration measured at 300 K was used in 4.2 and 120 K photoluminescence studies and the same procedure was followed by several authors [14,18,25,28]. P-type layers with thickness of about 1.2 mm were chosen for analysis to reduce thickness measurement errors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was observed that x is close to x G throughout the investigated range, which is in agreement with literature [21,22]. For lower growth temperatures and V/III ratios, XRD and PL could not be used for determination of the aluminum fraction, because high carbon concentrations lead to lattice contraction and a shift in the band gap [23,24]. In this parameter range, ICP-AES as performed at our institute seemed less reliable than SIMS.…”
Section: Methodssupporting
confidence: 86%
“…(3). Is important to comment that this equation is a semiempirical expression, which is a useful tool for determination of carrier concentration for shallow dopants [13,14]. However Mn is a deep acceptor in GaAs, therefore a comparison with carrier concentration obtained from the Hall measurements is necessary, and these values are plotted as solid circles in the inset of Fig.…”
Section: Resultsmentioning
confidence: 98%